Оценка современного состояния популяции Aconitum rogoviczii Wissjul. в национальном природном парке «Святые Горы» - Шпилевая, Н.В. (Промышленная ботаника, 2004)
Adaptive reactions of the population of protected Aconitum rogoviczii species to anthropogenic changes within the bounds of “Holy Mountains” national natural park have been investigated. Basic demographic - and - coenotic parameters of the species, such as density and age structure have been studied. The research of phenotypical variability has been conducted on the basis of some morphometric features of the given species individuals. The present-day state of Aconitum rogoviczii population and its development prospects have been estimated.